α,α-Difluoro-α-phenylsulfanyl-α- trimethylsilylmethane as "cF2-" synthetic building block for the preparation of gem-difluoromethylenated cyclopentanols - Krisana Peewasan (2018)
A general strategy for the preparation of gem-difluoromethylenated cyclopentanols has been demonstrated; it involves sequential fluoride-catalyzed nucleophilic addition of α,α-difluoro-α-phenylsulfanyl- α-trimethylsilylmethane (PhSCF 2 SiMe 3 ; 1) to homoallyl ketones followed by intramolecular radical cyclization. © 2011 Elsevier B.V. All rights reserved.